If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + 5) = 17x + 12 + -5x + 3 Reorder the terms: 3(5 + 4x) = 17x + 12 + -5x + 3 (5 * 3 + 4x * 3) = 17x + 12 + -5x + 3 (15 + 12x) = 17x + 12 + -5x + 3 Reorder the terms: 15 + 12x = 12 + 3 + 17x + -5x Combine like terms: 12 + 3 = 15 15 + 12x = 15 + 17x + -5x Combine like terms: 17x + -5x = 12x 15 + 12x = 15 + 12x Add '-15' to each side of the equation. 15 + -15 + 12x = 15 + -15 + 12x Combine like terms: 15 + -15 = 0 0 + 12x = 15 + -15 + 12x 12x = 15 + -15 + 12x Combine like terms: 15 + -15 = 0 12x = 0 + 12x 12x = 12x Add '-12x' to each side of the equation. 12x + -12x = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 6x+35+9x=15(x+2)-25 | | y+34=19 | | 3-9x=84 | | 5y+12-5=22 | | 2(-x+8)=24 | | 2x^2+162=0 | | 6(x+2)=2(3x+8)-4 | | 3x+4-5x-14=10 | | 7d-4d-4d-6=2d | | 11x+2=14x-10 | | 10y=40x+3xy | | 2(t-2)=6 | | 7x-y=(x) | | 0.5(x+2)-(3x+8)=1.6(x-2)+9 | | 3(7x+20Y)+7(-3x+6y)= | | y-37=-67 | | -21=n-10 | | 2(2x+5)=40 | | 3(x-5)=2(x+1)+x | | 5+9x=-13 | | -5.7-44.2=-8.3v | | -7y+3=8y+1 | | 3(7x+20Y)7(-3x+6y)= | | 4x+8-3x-10=-33 | | -6-2x-1=4x+8-6x-3 | | 2(n+5)=11 | | 7=-11+3(6+5) | | 2(n+5)=111 | | -5r-r=5r-8 | | 3x+5x+4x-2=10 | | -10x+8-6x=-2-17x+9 | | 5.4x+8.6=3.4x-16 |